1990
DOI: 10.1037/0022-3514.59.6.1238
|View full text |Cite
|
Sign up to set email alerts
|

The affective consequences of social comparison: Either direction has its ups and downs.

Abstract: Research on social comparison processes has assumed that a comparison in a given direction (upward or downward) will lead to a particular affective reaction. In contrast, the present two studies proposed and found that a comparison can produce either positive or negative feelings about oneself, independent of its direction. Several factors moderated the tendency to derive positive or negative affect from upward and downward comparisons. In Study 1, cancer patients low in self-esteem and with low perceived cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
545
5
13

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 714 publications
(600 citation statements)
references
References 61 publications
37
545
5
13
Order By: Relevance
“…Adding the upward comparison increased the variance explained to 25%, ⌬R 2 ϭ . 13, F(1, 58) (Buunk, Taylor, Dakof, Collins, & Van Yperen, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Adding the upward comparison increased the variance explained to 25%, ⌬R 2 ϭ . 13, F(1, 58) (Buunk, Taylor, Dakof, Collins, & Van Yperen, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Estudios iniciales indican una relación entre la variable OCS con los dominios social, físico y psicológico de la CV, no obstante, la varianza explicada de estos dominios por la OCS es baja (Urzúa, Castillo, Gemmel & Campos, 2010). Pese a esto, algunos estudios han referido posibles consecuencias en la esfera afectiva y en el bienestar psicológico derivado de las posibles formas de compararnos con otros (Buunk, Collins, Dakof, Taylor & VanYperen, 1990;Buunk, Gibbons, Belmonte, Peiró & Zurriaga, 2005;Buunk, Ybema, Gibbons & Ipenburg, 2001;Michinov, 2007). En este sentido, aquellos que tienden a compararse hacia arriba presentan mayores efectos negativos en sus afectos (Buunk, 2006;Buunk, Peiró, Rodríguez & Bravo, 2006), en tanto aquellos que se comparan hacia abajo, podrían generar mayor efecto positivo, especialmente cuando la persona que se compara está sometida a estrés o morbilidad (Buunk, 2006;Buunk & Ybema, 1997;Friedswijk, Buunk, Steverink & Slaets, 2004;Gibbons & alfonso urzúa m. & alEjandra caQuEo-urízar Buunk, 1999;Gibbons, Gerrard, Lando & McGovern 1991;Taylor, Wood & Lichtman, 1985; Van der Zee, Buunk & Sanderman, 1998;Van Yperen, Brenninkmeijer & Buunk, 2006;Wheeler & Miyake, 1992).…”
Section: D) CV = (Condiciones De Vida + Satisfacción Con La Vida) * Vunclassified
“…This characteristic gets special importance for comparison activity in old age, given that self-esteem is clearly at risk of decline in the elderly (Trzesniewski et al 2004). Buunk et al (1990) showed that the two directions of upward and downward social comparison are not intrinsically linked to affect and that under certain conditions both are capable of generating positive or negative affective responses. They argue that an upward comparison provides the information (a) that one is not as well off as everyone and (b) that it is possible to be better than at the present time.…”
Section: Motives Directions and Effects Of Social Comparisonsmentioning
confidence: 99%